2017
DOI: 10.1002/micr.30238
|View full text |Cite
|
Sign up to set email alerts
|

Suprafascial dissection of the pedicled groin flap: A safe and practical approach to flap harvest

Abstract: III (Therapeutic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Twenty patients were included in this study. In correlation to other studies, 30 patients were performed by Kimura [13], five patients by Green [14], six by Choi [15], 41 by Lee [16], and 28 by Abdelrahman [5]. The largest study group was 210 by Goh.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Twenty patients were included in this study. In correlation to other studies, 30 patients were performed by Kimura [13], five patients by Green [14], six by Choi [15], 41 by Lee [16], and 28 by Abdelrahman [5]. The largest study group was 210 by Goh.…”
Section: Discussionmentioning
confidence: 85%
“…The groin flap has the advantage of being a reliable & versatile flap for complex hand & forearm defects. As a pedicled flap, it is easy & fast to harvest with great outcome and easy to learn and to teach [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be one reason why some reconstructive surgeons do not use the groin flap as a free vascular tissue transfer on a regular basis. 20 However, due to its advantages of low donor-site morbidity combined with the good tissue pliability, we continue to employ this flap routinely. 20 It has been demonstrated that hypertension, peripheral arterial disease, as well as nicotine abuse are significant factors to worsen outcomes in microsurgical free flap procedures.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, due to its advantages of low donor-site morbidity combined with the good tissue pliability, we continue to employ this flap routinely. 20 It has been demonstrated that hypertension, peripheral arterial disease, as well as nicotine abuse are significant factors to worsen outcomes in microsurgical free flap procedures. [21][22][23][24] These findings could not be confirmed by us.…”
Section: Discussionmentioning
confidence: 99%